Intra‐Arterial Platelet Infusion for Intractable Hemorrhage and Refractory. Issue 12 (14th July 2015) - Kably, Issam M.; Ziga, Edward D.; Andreansky, Martin
<x xml:space="preserve">Abstract</x> Acute gastrointestinal graft‐versus‐host disease (GVHD) refractory to first‐line treatment with systemic corticosteroids results in increased morbidity and potential mortality. We retrospectively assessed the feasibility and efficacy of catheter‐directed intra‐arterial platelet infusion (IAPI) in two pediatric patients with steroid and transfusion refractory gastrointestinal GVHD causing intractable lower gastrointestinal hemorrhage and refractory thrombocytopenia, that were referred for salvage therapy. Immediate angiographic response was noted with a resolution of hemorrhage and decreased blood requirements. We reviewed the literature regarding this treatment modality and compared it to the available minimally invasive transcatheter techniques to control gastrointestinal hemorrhage. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.